Sosialisasi Pengetahuan Kesehatan Reproduksi pada Remaja SMAN 37 Maluku Tengah Tahun 2025 - Jusuf Leiwakabessy; Nathalie Elischeva Kailola; Carl Hein Huwaa; Fellicia Dominique Birahy; Nining Ayu Lestari; Victorius Y. Matital; Muhammad Sidiq Ainsa; Reka Febriani; Denisa Prisilia Silawane (Jurnal Pengabdian Masyarakat Waradin, 2026)
Adolescence represents a transitional phase characterized by complex biological, psychological, and social changes, during which insufficient understanding of reproductive health can lead to risky behaviors such as premarital sexual activity, unintended pregnancy, and sexually transmitted infections (STIs). The purpose of the activity titled “Reproductive Health Knowledge Socialization among Adolescents at SMAN 37 Central Maluku in 2025” was to enhance adolescents’ knowledge and awareness regarding reproductive health. This community service program employed a cross-sectional design and involved 54 students from grades X to XII, selected purposively. Data were collected through online pre-tests and post-tests using Google Forms, and the results were analyzed with Microsoft Excel to evaluate changes in participants’ knowledge levels. The findings revealed a notable increase in the average knowledge score from 76% to 89.8%, with the most significant improvements observed in aspects related to reproductive hygiene and understanding of STI risks. The activity proved effective in improving adolescents’ reproductive health literacy and strengthening their awareness of responsible reproductive behavior. Therefore, face-to-face interactive socialization serves as a strategic approach to reinforce healthy understanding and behavior among adolescents in archipelagic regions. Moreover, it can be adopted as a model for developing sustainable health education programs in schools across Eastern Indonesia.